Retroperitoneal Mass: A Diagnostic Challenge - Chakrabarti S, Ghosh S, Chakraborty J, D (Journal of Nepal Health Research Council, 2013)
We report a case of retroperitoneal mass involving lumbar spine (L2 region) of eight months duration in a male aged 26 years. X ray of the lumbar spine was suggestive of tuberculosis. However, as there was no response to specific therapy, a CT scan was performed which was indicative of a soft tissue sarcoma. Subsequent biopsy of the tumor showed it to be a giant cell tumor of bone (GCT). The tumor was inoperable and the patient is presently undergoing radiotherapy. Giant cell tumors only rarely arise in the axial skeleton. GCT of the spine is uncommon, accounting for 1.3-6.5% of all cases in various series. The case is being presented because of its rarity, diagnostic dilemma encountered and to emphasize the role of surgical biopsy.